PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI PADA SD NEGERI 2 JIWAN KARANGNONGKO KLATEN - Muriyanto, Muriyanto Muriyanto; Nurhayati, Tri (Jurnal As Sibyan, 2023)
The purpose of this research is to find out the implementation of Islamic religious education and morals at SD N 2 Jiwan Karangnongko Klaten. (Case study of obstacles and how to overcome them). Method This type of research is observation with a qualitative method where the data and research location are located at SD Negeri 2 Jiwan Karangnongko Klaten. The sample of this study was 19 people consisting of 8 girls and 11 boys who were in class VI at SD N 2 Jiwan Karangnongko Klaten. The methods used in this study are: Observation, Interview and Documentation. The data analysis techniques in this study were data reduction, data presentation. Research showing the implementation of learning Islamic Religious Education and Characteristics of SD N 2 Jiwan Karangnongko Klaten (Case Study of obstacles and how to overcome them) teachers use the lecture method, discussion method, and jigsaw cooperative method. The obstacles include: students who are easily bored in this learning, teachers who are less professional, less infrastructure, and an incomplete school environment. The way to overcome this is by motivating students, educators use various methods in class learning, increase the professionalism of educators with independent learning and actively participate in training to enrich insights, complete educational facilities and infrastructure, the school environment by providing activities that can support student learning in class . From these results the category is good with an average value of 82.42.